Early-onset gynecological tumors in DNA repair-deficient xeroderma pigmentosum group C patients: a case series - Andrey. A. Yurchenko; Brice Fresneau; Bruno Borghese; Fatemeh Rajabi; Zora Tata; Catherine Genestie; Alain Sarasin; Sergey I. Nikolaev (Communications Medicine, 2023)
Abstract Background Xeroderma pigmentosum (XP) is a group of rare hereditary disorders with highly increased risk of skin tumors due to defective DNA repair. Recently we reported 34-fold increased risk of internal tumors in XP patients in comparison with general population. The molecular data and clinical practice on the internal tumors treatment in XP patients is limited and scarcely represented in the medical literature. In this work, we describe young patients with constitutive biallelic deactivation of the XPC gene developing gynecological tumors with somatic DICER1 mutations. Methods Whole genome sequencing was used to analyze in detail somatic mutational landscape and driver events of these rare tumors. Results We describe five early-onset gynecological tumors in four xeroderma pigmentosum group C (XP-C) young patients (11 to 19 years old) including vaginal embryonal rhabdomyosarcomas in monozygotic twin sisters, juvenile granulosa-cell tumor of the ovary and poorly differentiated stage IA Sertoli-Leydig cell tumor in 19-years old patient, and FIGO stage IC1 tumor of ovary in 13-years old patient. XP-C ovarian tumors harbor 4.4 times more single base substitutions than sporadic tissue-matched cancers and demonstrate XP-C specific mutation signature with strong transcriptional bias indicating inability of the cells to repair bulky DNA lesions of unknown etiology. A special mode of treatment was applied to avoid usage of chemotherapy which is toxic for XP patients. Conclusions XP-C status should be accounted for prevention and specific treatment of gynecological tumors in young DNA repair-deficient XP patients.